Economic and agrometeorological modeling of sugarcane productivity in SAo Paulo state, Brazil - Fernandes Figueira, Sergio Rangel [UNESP]; Rolim, Glauco de Souza [UNESP] (Wiley-Blackwell, 2020)
Sugarcane (Saccharum officinarum L.) productivity is dependent on climatic and economic conditions. The goal of this research is to combine economic and agrometeorological modeling on sugarcane productivity in the 18 important sugarcane production microregions of the SAo Paulo state in Brazil from 1995 to 2012. Cluster analysis was used to identify two groups of microregions with similar sugarcane actual productivity (PR) within each group. Group 1 presented higher values compared to group 2 in all years. However, the sugarcane attainable productivity (PA), estimated by the agrometeorological model, of group 2 was higher than group 1 in 17 of the 18 years analyzed. Finally, a statistical model was used to quantify the influence of sugarcane price, rural credit concession and PA on PR in all microregions and in the two groups. For all microregions, sugarcane price was the most important explanatory variable for PR, followed by PA and the rural credit concession in third. PR of Group 1 was mainly affected by sugarcane prices and PR of group 2 was mainly affected by PA. Therefore, the group 1 sugarcane producers were able to respond to price changes regardless of PA in this group. This can occur due to a better management, bigger investments or smaller metereological adversity of group 1. In conclusion, the agrometereological (PA) and the economic (sugarcane price and rural credit concession) variables affected the PR in the analyzed regions. However, crop pathogens, meteorological adversities or human management have led to this situation (limiting and reducing factors).